Molecular study of endophytic Aspergillus terreus isolated fromGlycyrrhiza glabra plant - Ali, Israa Ahmed (Iraqi Journal of Science, 2025)
Plants contain many types of endophytic fungi, and these have several applications in farming and biofuel production. Vegetables, trees, fodder, fruits, cereal grains, and wild plants, including Glycyrrhiza glabra, harbor them. The present study was conducted to isolate and molecularly characterize Aspergillus terreus from Glycyrrhiza glabra plant roots obtained from Al-Jadiria Company gardens in Baghdad, Iraq. Twenty healthy Glycyrrhiza glabra plant samples were collected from various locations in Al-Jadiria Company gardens in Baghdad, Iraq. Endophytic fungi were isolated from the root samples. Morphological and microscopic examination were used to identify the fungal isolates. The identification of the fungal isolates was confirmed using molecular analysis. Polymerase chain reaction (PCR) was used to amplify the internal transcribed spacer (ITS) region of the rRNA gene. The PCR product was purified and sequenced. The nucleotide sequence was subjected to bioinformatics analysis. The results revealed that 70% (14\20) of the Glycyrrhiza glabra plant root samples tested positive for Aspergillus species according to the morphological and microscopic examination. A fragment size of 650 bp was obtained by amplifying the ITS region of the rRNA gene. The bioinformatics analysis confirmed that the endophytic fungus was Aspergillus terreus. After amplification of fungi's ribosomal RNA, primers (ITS) and phylogenetic structuring tree analysis were carried out by sequences and confirmation of microorganism homogeneous data utilizing a database (NCBI). The results indicated that when compared to the wild type of the ITS gene from the gene bank, Aspergillus terreu isolate IAA1 small subunit ribosomal RNA gene displayed 100% identity.